Design of a genetic microstrip patch antenna with broadside radiation for GSM applications - Jayasinghe, Jeevani; Uduwawala, Disala; Anguera, Jaume (International Journal of Scientific World, 2014)
Designing multiband antennas with broadside radiation becomes of practical interest in the ever growing wireless communication. In this regard, design of a multiband microstrip patch antenna (MPA) for GSM850, GSM900, GSM1800 and GSM1900 applications using Genetic Algorithms (GA) combined with Finite Element Method (FEM) is proposed to optimize the patch geometry and the feed position. A substrate with dielectric constant 3.2 and height 0.76 mm is used to support the MPA. Patch dimensions are (100 mm × 122 mm) similar to that of the conventional rectangular patch for the lowest frequency band (GSM850). In addition, there is an air gap of 10 mm between the substrate and the ground plane. This MPA with a reflection coefficient less than -10 dB and broadside radiation at all four GSM bands can be useful for base station antennas. Keywords: Genetic Algorithm Optimization; GSM; Microstrip Patch Antennas; Mobile Communication.